Respuesta :
[tex]▪▪▪▪▪▪▪▪▪▪▪▪▪ {\huge\mathfrak{Answer}}▪▪▪▪▪▪▪▪▪▪▪▪▪▪[/tex]
Let's evaluate :
- [tex] {2x}^{3} + 5x {}^{2} - 10 [/tex]
- [tex]2( - 2) {}^{ 3} + 5( - 2) {}^{2} - 10[/tex]
- [tex](2 \times - 8) + (5 \times 4) - 10[/tex]
- [tex] - 16 + 20 - 10[/tex]
- [tex] - 26 + 20[/tex]
- [tex] - 6[/tex]
Hey there!
2x³ + 5x² - 10
It's given that the value of x is -2. So substitute it in the place of x in the equation.
2(-2)³ + 5(-2)² - 10
= 2 × -8 + 5 × 4 - 10
= -16 + 20 - 10
= 4 - 10
= - 6
Hope it helps ya!